Karakteristik Polen pada Spesies Mangrove di Kawasan Hutan Mangrove Batu Lumbang, Denpasar, Bali - Pramesti, Ni Kadek Rika; Wijaya, I Made Saka; Gari, Ni Made (Bumi Lestari; Vol 24 No 1 (2024)DO - 10.24843/blje.2024.v24.i01.p05, 2024)
The diversity of mangrove species in an area can be observed through morphological structure, anatomy, as well as palynology. Palynology is a study of pollen that frequently used as a reference to support data in identifying mangrove species. Mangrove areas in Bali have patchy distribution, one of which can be found in the Batu Lumbang area. Batu Lumbang is a mangrove area that is part of the Ngurah Rai Forest Park. Observation of the micromorphological characteristics of pollen in the Batu Lumbang mangrove forest area was carried out through the acetolysis method with modification. Eleven mangrove species were sampled, comprised of Aegiceras corniculatum , Avicennia marina , Bruguiera gymnorhiza , Ceriops tagal , Exoecaria agallocha , Lumnitzera racemosa , Rhizophora apiculata , Rhizophora mucronata , Sonneratia alba , Sonneratia caseolaris , and Xylocarpus granatum . The results of observations on pollen from eleven species of mangroves show similarities of pollennits, monads. In addition, other pollen characters such as aperture type, pollen shape, and pollen size categories found vary among the samples observed. These characters can also group several species that have the same family or genus. In turns, these can be used as diagnostic character to distinguish one species with another.